Technology Adoption in Local Governance: Moderating Effects of Readiness for Change on Digital Leadership and Information Technology Capability - Anedi, Achmad Edwyn; Suparto Wijoyo; Setijaningrum, Erna (Dinasti Review, 2025)
This study investigates the adoption of digital technology in Indonesian village governance, specifically through the